2015
DOI: 10.14202/vetworld.2015.881-887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deep litter housing and fermented feed on carcass characteristics and meat quality of crossbred Hampshire pigs

Abstract: Aim:The objective of the study was to evaluate the effect of deep litter housing and fermented feed on carcass characteristics and meat quality of crossbred Hampshire pigs.Materials and Methods:Forty-eight weaned crossbred Hampshire piglets of 2 months age (24 males and 24 females) were selected for the experiment. The piglets were randomly assigned into 4 homogenous experimental groups with 6 males and 6 females each: E1; reared on a conventional housing and fed with a fermented diet, E2; reared on a deep lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Supplementing with FF has been dramatically investigated to improve the feed digestibility, balance intestinal microbiota, stay gut health and modulate immunity, thereby benefiting swine health and performance (Canibe and Jensen, 2003; Missotten et al ., 2015; Rahman et al ., 2015). Lactation period of sows is an important stage of swine breeding (Tokach et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing with FF has been dramatically investigated to improve the feed digestibility, balance intestinal microbiota, stay gut health and modulate immunity, thereby benefiting swine health and performance (Canibe and Jensen, 2003; Missotten et al ., 2015; Rahman et al ., 2015). Lactation period of sows is an important stage of swine breeding (Tokach et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial fermentation using bacteria or fungi is capable of degrading antinutritional compounds, undigested components, and some large-size nutrients in feed while providing probiotics and their metabolites (Urlings et al, 1993;Olstorpe et al, 2010;Kiarie et al, 2011). Feeding FF has been well established to increase the bioavailability of feed, improve swine microbial ecology balance, enhance gut health, and decrease diarrhea rate and thereby benefit growth performance and host health (Canibe and Jensen, 2003;Kiers et al, 2003;Rahman et al, 2015;Missotten et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the consumer's health becomes at stake because of contaminated milk harboring pathogens (OIE Animal Production Food Safety Working Group, 2006). Bedding surface is also responsible for the contamination of animal hides (Ward et al, 2001), which take these pathogens to slaughterhouses, directly posing a risk of foodborne illness [12,13]. The production of different gasses in different beddings also has a significant contribution to animal, workers and environmental health [4].…”
Section: Mini Reviewmentioning
confidence: 99%
“…Studies have shown that pigs reared in deep litter system consisting of sawdust show better performance and meat quality making it an economical solution and welfare perspective [13]. Moreover, sawdust is used as bedding in pig farms and transport vehicles, and it doesn't seem to enhance aggressive behavior or decrease welfare of animals [33,34].…”
Section: Sawdustmentioning
confidence: 99%